THE HEALTH IMPACT OF TOURISM ON THE PSYCHOPHYSICAL STATE OF ELDERLY INDIVIDUALS - Hakman, A.; Andrieieva, O.; Balatska, L.; Filak, F.; Filak, Y.; Tivelik, M.; Bezverkhnia, H.; Tsybulska, V.; Koshura, A.; Savchuk, S.; Medvid, A. (Journal of Sport and Health Research, 2024)
Scientific developments by experts in the fields of medicine, physical culture, and psychology indicate that tourism is an important tool for supporting health and mental well-being. It helps individuals enjoy life, remain active and maintain a positive mood throughout their life activities. The purpose of our research is to ascertain the impact of tourism activities on the psychophysical state of elderly individuals. The goal of our study is to determine the impact of tourism activities on the psychophysical condition of the elderly age people. Materials and methods. 221 people took part in the transformative experiment aged 60-65, who attend the University of the Third Age (152 women and 69 men). It is worth mentioning that the frequency of classes at the University of the Third Age was 3 classes per week, lasting 40-60 minutes. During the practical classes, considerable attention was paid to the psycho-emotional state and technical performance of physical exercises with the correct breathing technique. The main purpose of this experiment was to increase the effectiveness of the tourism impact on the University of the Third Age. The establishment of conditions for the creative, intellectual, spiritual and physical development of the elderly population, development of physical qualities, health prevention, formation of a healthy lifestyle, rational organization of health-recreational motor activity in free time. The program is designed for 6 months and consists of preparatory (adaptation), main (improvement) and supporting periods. Each of the periods was aimed at achieving a set of tasks. To assess the quality of life, the Medical Results Questionnaire by using the Short Form (SF-36) was used. To assess the satisfaction of the participants' lives, the Life Satisfaction Index A (LSIA), developed by Bernice L. Neugarten et al., was used (1961) and adapted by N.V. Panina (1993). Physical activity was evaluated using the PWC150 test. The level of success in psychosocial adaptation was assessed using a modified Rogers and Diamond questionnaire. Mind performance was assessed using Bourdon's correction test. The Wilcoxon test was used to analyze the statistical significance of the differences between the data. In each case, the hypothesis was tested, and the p-value was calculated. Conclusions regarding the significance of testing were made at the 0.05 significance level. The results. In the conditions of the University of the Third Age, during the implementation of the concept, positive dynamics of indicators of motor activity, quality and satisfaction with life, mental and physical working capacity, rates of aging, socio-psychological adaptation, cognitive functions, psycho-emotional state were fixed. However, we note significant changes in integral indicators of socio-psychological adaptation at the end of the study, namely, in the indicators of self-perception (women – 68.8 ± 0.7 points; men – 78.8 ± 4.1 points) and emotional comfort (women 63.3 ± 1.7 points ; men 69.2 ± 1.2 points) (p=0.05). As was anticipated, for elderly individuals who continue self-education in their later years, the tourism program had a positive impact on cognitive functioning indicators. Taking into considerations the women’s segment, 7.9% corresponded to a very high level of mental capacity, and 17.4% to a high level. Considering men, a very high level of mental capacity corresponded to 13.0%, high - 31.9%; (p=0.05). Conclusion. Involvement in health tourism has a positive impact on the psychophysical state of elderly individuals. The combination of physical activity, social interaction and the acquisition of new experiences contributes to the improvement of emotional, physical and cognitive health.
LA INFLUENCIA DEL TURISMO EN LA SALUD DEL ESTADO PSICOFÍSICO DE LAS PERSONAS DE TERCERA EDAD
Keywords: old age, physical activity, tourism